PERENCANAAN KAWASAN KOLONG RETENSI KACANG PEDANG SEBAGAI KAWASAN WISATA DANAUDI KOTA PANGKALPINANG, KEP. BANGKA BELITUNG - Hafiz Satriadi, - (2010)
The exploitation of tin mining which had happened since the Colonialism in Bangka Island has just left the dig trace like a lake, and it was called as "Kolong" or Hollow by the people there. The Hollows, was spread in all places in Bangka Island including Pangkalpinang. The "Kolong Retensi Kacang Pedang" which had revitalization to a retention area and it was functioned as water reservoir from Rangkui River stream flow. The Kolong Retensi Kacang Pedang was used as raw water sources to the people of Pangkalpinang. If the nature potential of Kolong Retensi Kacang Pedang had properly planned, it will give the positive effect to the people, government, and the private sector. The method used is descriptive qualitative approach using the analysis of tourism potential of Kolong Retensi Kacang Pedang using the Spardley chart. This is done as a test of the validity of each process and the data has been obtained. The analysis of the approach of tourist potential was used for the existing tourism potential in Kolong Retensi Kacang Pedang. Planning area Kolong Retensi Kacang Pedang as tourism lakes must consider the rules from the protection of nature; since this area is the area of raw water sources for the community of Pangkalpinang City. Conservation and the creation of harmony with nature tourism areas around planned according to the values of sustainable tourism. The existence of the establishment of mangrove forests around the area can be an attraction for tourists and is one way in nature conservation. The division uses the concept of zoning area honey pot and divides the region into the core zone, service zone, and buffer zones.